1993
DOI: 10.1093/protein/6.5.471
|View full text |Cite
|
Sign up to set email alerts
|

The structure of a designed peptidomimetic inhibitor complex of α-thrombin

Abstract: Thrombin displays remarkable specificity, effecting the removal of fibrinopeptides A and B of fibrinogen through the selective cleavage of two Arg-Gly bonds between the 181 Arg/Lys-Xaa bonds in fibrinogen. Significant advances have been made in recent years towards understanding the origin of the specificity of cleavage of the Arg16-Gly17 bond of the A alpha-chain of human fibrinogen. We have previously proposed a model for the bound structure of fibrinopeptide A7-16 (FPA), based upon NMR data, computer-assist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…In contrast to the abundance of crystal structures of complexes between thrombin and chemical inhibitors (33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45), our structure is only the second structure of the inhibitor-bound factor Xa. The structure of the DX-9065a-bound factor Xa was the first inhibitor complex structure published (13).…”
Section: Discussionmentioning
confidence: 96%
“…In contrast to the abundance of crystal structures of complexes between thrombin and chemical inhibitors (33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45), our structure is only the second structure of the inhibitor-bound factor Xa. The structure of the DX-9065a-bound factor Xa was the first inhibitor complex structure published (13).…”
Section: Discussionmentioning
confidence: 96%
“…Examination of x-ray crystal structures of proteolytic enzymes and their endogenous inhibitors (i.e., serpins, Kunitz inhibitors) has demonstrated that an extended strand motif is uniformly adopted by the inhibitor/pseudo-substrate in the enzyme-active site (35,36). A ␤ strand template library enables development of potent specific inhibitors of proteolytic enzymes, such as thrombin, factor VIIa, urokinase-type plasminogen activator, hepatitis C virus protease, and caspase 3 (24,37).…”
Section: Discussionmentioning
confidence: 99%
“…One-third of all compounds are proposed to adopt a II or II@ turn type (1,5,7,8,12,16,21,23,31,32,36) and three are designed to mimic a I or I@ turn (13,28,37). All other compounds can either substitute for several kinds of turn or are intended to achieve a chain reversal.…”
mentioning
confidence: 99%
“…Eight compounds turned out to be weak or inactive ligands (6,7,9,15,30,33,36,37). The conformations of most of the compounds have been conÐrmed by X-ray structure determination (1, 9È11, 16,19,21,23,28,29,35), NMR spectroscopy (3È6, 12, 13, 17, 20, 22, 26, 27, 30È32, 34, 36) or modelling studies (7,8,14,24,33,37). Surprisingly, to the best of our knowledge, there is only one example (compound 28) where the predicted and the experimentally determined structure of the protein (thrombin) in complex with the ligand was published.28 The importance of peptidomimetics for peptide research is not questioned.…”
mentioning
confidence: 99%